Sentence Structure of Serawai Language in the Folklore “Mulan Deghian Kejujuran” by Zazili Mustopa - Arvischa Thifanny Aghisa; Elyusra; Man Hakim; Ajat Manjato (JLER (Journal of Language Education Research), 2024)
The Bengkulu regional language used in the folklore book titled Mulan Deghian Kejujuran is Serawai language. The issue addressed in this research is the sentence structure of Serawai language in folklore of Mulan Deghian Kejujuran by Zazili Mustopa. The objective of this study is to obtain a precise, detailed, and in-depth understanding of the description of the sentence structure in the folklore of Mulan Deghian Kejujuran Karya Zazili Mustopa. The employed method in this research is te descriptive qualitative method. The data source for this study is the folklore book Mulan Deghian Kejujuran authored by Zazili Mustopa, published by the Ministry of Education, Culture, Research, and Technology, Language Office of Bengkulu Province in 2022. The techniques of data collection encompass reading and note-taking. The process of data analysis involved the identification of sentence structure patterns, interpretation of these patterns, and the compication of sentence structure data. The research findings demonstrate that the Serawai language sentences in this folktale have 17 distinct sentence structure patterns. Among these, the J (S-P-O) pattern is more prominently utilized in the Mulan Deghian Kejujuran folktale authored by Zazili Mustopa.